Strategic Management Strategies in Nonformal Education Program Administration in Indonesia’s 3T Region - Abednego Abednego; Alberthina Abetsi Haumahu; Heldy Ivana Laturake (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study examines strategic management practices in the administration of nonformal education programs within Indonesia’s 3T regions areas characterized by geographical isolation, limited infrastructure, and socioeconomic challenges. The research aims to identify effective management strategies that enhance institutional sustainability, leadership performance, and community participation in nonformal educational settings. Employing a qualitative narrative review approach, this study synthesizes findings from 45 peer-reviewed publications published between 2019 and 2025, encompassing themes of adaptive management, participatory leadership, policy integration, and digital innovation. The analysis reveals that institutions adopting flexible and context-responsive strategies supported by collaborative governance and technological integration demonstrate higher resilience and alignment with local educational needs. Furthermore, the review highlights the importance of leadership adaptability, stakeholder engagement, and community-based governance as central pillars for achieving sustainable education outcomes in resource-limited contexts. The study contributes theoretically by proposing a model of “localized strategic adaptability,” which integrates principles of strategic management with participatory education governance, and practically by offering evidence-based insights to guide policymakers and administrators in strengthening nonformal education systems.